Oh ! Do you want to have a short cut way for mathematics ………identities. World of identities

Slide 2:

Do you have the pre-requisite knowledge for expansion of (a+b)2
a2+2ab+b2
What is the volume of cube of side “a”?
a3

What is an Identity ? :

What is an Identity ? Consider the equality (a+1)(a+2)= a 2+3a+2
We shall evaluate both sides of this equality for some value of a, say a=10.
For a=10, LHS= (a+1)(a+2)= (10+1)(10+2)
= 11x12=132
RHS= a 2+3a+2=10 2+3x10+2
=100+30+2=132
We shall find for any value of a, LHS =RHS. Such an equality, true for every value of the variable in it, is called an identity.
Thus (a+1)(a+2)= a 2+3a+2 is an identity

What are identities ? :

What are identities ? These are the mathematical equations which are satisfied by all values of variables.

Algebraic proof of identity. :

Algebraic proof of identity. Let us derive (a+b)3
We know that, (a+b)2=a2+2ab+b2.
But, (a+b)3=(a+b)2(a+b).
Therefore, (a+b)3=(a2+2ab+b2)(a+b).
= a2(a+b)+2ab(a+b)+b2(a+b)
= a3+a2b+2a2b+2ab2+ab2+b3
= a3+3a2b+3ab2+b3
= a3+3ab(a+b)+b3

Geometric proof of identity. :

Geometric proof of identity. a a b b b Aa VOLUME V=a3 VOLUME V=b3 Total volume V1=a3+b3 a

Slide 7:

a a b b a a b V=a2b V=a2b V=a2b Therefore Total volume of the
Cuboides
V2=a2b+a2b+a2b=3a2b a a

Slide 8:

a b b a b b a b b V=ab2 V=ab2 V=ab2 Therefore V3=ab2+ab2+ab2=3ab2.

Slide 9:

A B a b b C b a E b a G F a3 b3 a2b a+b a+b a+b After arranging jumbled cubes & cuboides……………
WE GET…….. a Therefore V=(a+b)3 But from V1 V2 V3 we have V=V1+V2+V3 (a+b)3=a3+3a2b+3ab2+b3 =a3+3ab(a+b)+b3
Therefore proved.

USE OF IDENTITIES. :

USE OF IDENTITIES. Find the expansion of (x+5)3
Here a=x b=5
(a+b)3=a3+3ab(a+b)+b3
Therefore (x+5)3=x3+3(x)(5)(x+5)+(5)3
=x3+15x(x+5)+125
=x3+15x2+75x+125

USE OF IDENTITIES IN DAILY LIFE. :

USE OF IDENTITIES IN DAILY LIFE. Find the cube of 102
1023=(100+2)3
a=100 b=2
(a+b)3= a3+3ab(a+b)+b3
(100+2)3= (100)3+3(100)(2)(100+2)+(2)3
1023 =1000000+600(102)+8
=1000000+61200+8
=1061208

Slide 12:

PASCAL'S TRIANGLE a a + b (a + b)2 = a2 + 2ab+b2 (a + b)3 = a3 + 3a2 b+3ab 2 +b3 (a + b)4 = a4 + 4a3b + 6a2 b2 +4ab3+b 4 (a + b)6 = ------------------------- (a + b)5 =-------------------------- It helps us to write expansion form of the identity (a + b)n

You do not have the permission to view this presentation. In order to view it, please
contact the author of the presentation.